Il ducato di Filippo Maria Visconti, 1412-1447. Economia, politica, cultura - Cengarle, Federica; COVINI, MARIA NADIA (Reti Medievali E-Book, 2015)
The domination of Filippo Maria Visconti in Lombardy (1412-1447) was the result of an attempt, only partially successful, to recompose the vast territories already dominated by the first duke, Giangaleazzo Visconti. For thirty-five years, the third duke of Milan governed a large, rich and prosperous state, strengthened its institutions, cultivated high monarchical ambitions and proclaimed ideas of peace, concord and justice. The use of force and diplomacy and the close confrontation with the political, social and economic actors of the domain were the tools adopted to strengthen and consolidate the ducal domination. The authors of this volume illustrate the political models underlying the exercise of the duke's authority, the ways of establishing relationships between authorities and subjects, the construction of the symbolic and ideological apparatus, the artistic commission of the prince, ecclesiastical politics and the religious events of the duchy against the background of the councils of Constance and Basel. Some specific moments of ducal politics are also analyzed: the deeds of dedication of 1412, the geopolitical set established in 1435 after the victory of Ponza, the crisis of the last years of the duchy characterized by the ruthless execution of the government practices. Ultimately, the book aims to offer a more in-depth and problematic view of the domination of the third duke of Milan, which in its chiaroscuro turns out to be an important moment in the stabilization of the structures of the Lombard regional state.